2009
DOI: 10.1111/j.1365-313x.2009.03863.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxule extension over ER‐defined paths constitutes a rapid subcellular response to hydroxyl stress

Abstract: SUMMARYPlants survive against myriad environmental odds while remaining rooted to a single spot. The time scale over which plant cells can respond to environmental cues is seldom appreciated. Fluorescent protein-assisted live imaging of peroxisomes reveals that they respond within seconds of exposure to hydrogen peroxide and hydroxyl radicals by producing dynamic extensions called peroxules. Observations of the Arabidopsis flu mutant and treatments with xenobiotics eliciting singlet oxygen and superoxide react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
153
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(162 citation statements)
references
References 52 publications
(76 reference statements)
8
153
1
Order By: Relevance
“…There is evidence to suggest that ROS are involved in regulating peroxisome proliferation, as some peroxisomal biogenesis genes (PEX) are transcriptionally regulated by H 2 O 2 in both plant and animal cells (López-Huertas et al, 2000). The formation of peroxisomal extensions, known as peroxules, has also been observed to be regulated by exogenous applications of H 2 O 2 (Sinclair et al, 2009;Barton et al, 2013). The term "peroxule" was coined by Scott et al (2007) to refer to dynamic extensions, which are similar to those observed in chloroplasts (stromules).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence to suggest that ROS are involved in regulating peroxisome proliferation, as some peroxisomal biogenesis genes (PEX) are transcriptionally regulated by H 2 O 2 in both plant and animal cells (López-Huertas et al, 2000). The formation of peroxisomal extensions, known as peroxules, has also been observed to be regulated by exogenous applications of H 2 O 2 (Sinclair et al, 2009;Barton et al, 2013). The term "peroxule" was coined by Scott et al (2007) to refer to dynamic extensions, which are similar to those observed in chloroplasts (stromules).…”
mentioning
confidence: 99%
“…The term "peroxule" was coined by Scott et al (2007) to refer to dynamic extensions, which are similar to those observed in chloroplasts (stromules). It has been 1 suggested that peroxules are involved in the elongation of peroxisomes (Sinclair et al, 2009), although little is known about the function and regulation of peroxules. Furthermore, the speed of peroxisome movement can change under stress conditions imposed by Cd and herbicide 2,4-D and is also regulated by ROS (Rodríguez-Serrano et al, 2009.…”
mentioning
confidence: 99%
“…Moreover, peroxules can respond to environmental signals. For example, peroxules are induced by oxidative stress (Sinclair et al, 2009), and high light rapidly induces peroxule interactions with mitochondria (Jaipargas et al, 2016). The study of peroxule dynamics is in its infancy, and how proteins on the peroxisome and target organelle mediate these interactions awaits discovery.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Additionally, PEX11a is implicated in forming peroxisomal membrane extensions called "peroxules" (Rodríguez-Serrano et al, 2016). Peroxule formation is induced by ROS (Sinclair et al, 2009;Rodríguez-Serrano et al, 2016) and may promote the peroxisomal elongation that precedes division (Fig. 2).…”
Section: Peroxisome Division and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation